Smarter and Prosperous: Digital Transformation and Enterprise Performance - Gao, Da; Yan, Zhiliang; Zhou, Xiaotian; Mo, Xinlin (Systems (Basel), 2023)
Using manually constructed enterprise digital data from 2012 to 2020, this paper innovatively constructs an enterprise digitalization index to explore its impact on enterprise performance and discusses the potential channels of digitalization on enterprise performance. The findings show that (1) digitalization has a significant positive effect on firm performance, and this finding holds after a series of robustness tests. (2) Digitalization improves firm performance by reducing external management costs and strengthening internal controls. The mediating effects model tests the potential impact mechanism of digitalization on firm performance. (3) The effect of digitalization on the performance of state-owned enterprises is greater than for non-state-owned enterprises. The results of the heterogeneity analysis provide policy recommendations for the development of digital transformation of enterprises. Overall, this study provides new insights into the relationship between digitalization and firm performance.